Wntless promotes bladder cancer growth and acts synergistically as a molecular target in combination with cisplatin - Schmid, Sebastian C.; Sathe, Anuja; Guerth, Ferdinand; Seitz, Anna-Katharina; Heck, Matthias M.; Maurer, Tobias; Schwarzenboeck, Sarah M.; Krause, Bernd J.; Schulz, Wolfgang A.; Stoehr, Robert; Gschwend, Juergen E.; Retz, Margitta; et al. (Urologic Oncology-Seminars and Original Investigations, 2017)
To analyze the contribution of Wnt signaling pathway to bladder cancer growth in order to identify suitable target molecules for therapy.Expression of Wnt 2/4/7, LRP5/6, TCF1/2/4, LEF-1, and ?-actin was detected by reverse transcription polymerase chain reaction in a panel of 9 and for Wntless (WLS) in 17 bladder cancer cell lines. Protein expression of WLS was detected in 6 cell lines. Wnt/?-catenin activity was analyzed using the TOPflash/FOPflash luciferase reporter assay. Expression level of ?-catenin, WIF1, Dickkopf proteins (DKK), HSulf-2, sFRP4, and WLS was modulated by transfecting or infecting cells transiently or stably with respective shRNAs, siRNAs, or cDNAs. For protein detection, whole cell lysates were applied to sodium dodecyl sulfate polyacrylamide gel electrophoresis followed by immunoblots. Effects on cell growth were determined by cell viability assays and BrdU/APC incorporation/staining. For 3-dimensional tumor growth, the chicken chorioallantoic membrane model was used. Tumor growth was characterized by weight.Expression of molecular components and activation of the Wnt signaling pathway could be detected in all cell lines. Expression level of ?-catenin, WIF1, DKK, WLS, and HSulf-2 influenced Wnt activity. Expression of WLS was confirmed in 17 cell lines by reverse transcription polymerase chain reaction and in 6 cell lines by immunoblotting. WLS positively regulates Wnt signaling, cell proliferation, and tumor growth in vitro and in vivo. These effects could be reversed by the expression of the Wnt antagonist WIF1 and DKK. Synergistic activity of cisplatin and WLS inactivation by genetic silencing could be observed on cell viability.The Wnt signaling pathway is ubiquitously activated in bladder cancer and regulates tumor growth. WLS might be a target protein for novel therapies in combination with established chemotherapy regimens.
EVALuna2:6905